2018
DOI: 10.1002/adbi.201800049
|View full text |Cite
|
Sign up to set email alerts
|

Receptor‐Targeted Drug Delivery and the (Many) Problems We Know of: The Case of CD44 and Hyaluronic Acid

Abstract: CD44 is best known for being the most common receptor of hyaluronic acid (HA). It is also a heterogeneous molecule: while its standard isoform (CD44s) is ubiquitously expressed, there are also a range of variants (CD44v), and both CD44s and CD44v undergo a variety of post‐translational modifications. The signaling roles and frequent overexpression of both CD44s and CD44v in cancer (e.g., in cancer initiating cells/cancer stem cells) has raised interest in them for diagnostic applications, but also—and most imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 309 publications
0
8
0
Order By: Relevance
“…Due to its tumorigenic functions and level of expression often associated with tumor-initiating cells/cancer stem cells, CD44 is considered an early indicator for cancer cell proliferation (Basakran, 2015 ; Rios De La Rosa et al., 2018 ). This establishes CD44 as a biomarker in cancer diagnosis, particularly for breast, colorectal, head and neck, pancreas, bowel and prostate cancers (Rios De La Rosa et al., 2018 ). CD44 has a high affinity for HA, and all isoforms of CD44 contain an HA-specific binding domain near the N terminus (Lintuluoto et al., 2021 ).…”
Section: Approaches For Target-specific Drug Deliverymentioning
confidence: 99%
“…Due to its tumorigenic functions and level of expression often associated with tumor-initiating cells/cancer stem cells, CD44 is considered an early indicator for cancer cell proliferation (Basakran, 2015 ; Rios De La Rosa et al., 2018 ). This establishes CD44 as a biomarker in cancer diagnosis, particularly for breast, colorectal, head and neck, pancreas, bowel and prostate cancers (Rios De La Rosa et al., 2018 ). CD44 has a high affinity for HA, and all isoforms of CD44 contain an HA-specific binding domain near the N terminus (Lintuluoto et al., 2021 ).…”
Section: Approaches For Target-specific Drug Deliverymentioning
confidence: 99%
“…As a consequence, the targeting capacity of HA is rather unspecific. [94,95] Despite this, several works have shown that HA-based nanosystems tend to accumulate in the tumor tissue, which could be also caused by its stealth properties, or a combined effect of these active and passive mechanisms. [93] The first report in this line showed that HA-coated liposomes encapsulating mitomycin C were more efficacious than the un-coated carriers, in different murine cancer models (colon, melanoma, and lung metastasis).…”
Section: Relevant Nanocarriers Targeting Tumor Cellsmentioning
confidence: 99%
“…CD44 is a surface protein responsible for interaction between cells and also plays vital role in the adhesion and migration of the cells ( 137 ). The CD44 has a specific binding site for hyaluronic acid which facilitates interaction with selectin, osteopontin, fibronectin, laminin, and collagen in the extracellular matrix ( 138 ). The binding of hyaluronic acid with CD44 results in the activation of epidermal growth factor receptor family kinases such as the MAPK and PI3/AkT that in turn promotes growth and proliferation in various cancers ( 138 ).…”
Section: Micrornas As Master Regulator Of Stemness and Metastasismentioning
confidence: 99%
“…The CD44 has a specific binding site for hyaluronic acid which facilitates interaction with selectin, osteopontin, fibronectin, laminin, and collagen in the extracellular matrix ( 138 ). The binding of hyaluronic acid with CD44 results in the activation of epidermal growth factor receptor family kinases such as the MAPK and PI3/AkT that in turn promotes growth and proliferation in various cancers ( 138 ). Majority of CSCs population have CD44 surface markers along with other cell surface markers that increase invasiveness and stemness ( 139 ).…”
Section: Micrornas As Master Regulator Of Stemness and Metastasismentioning
confidence: 99%